Migingo Island Border Dispute in East Africa: A Comparative Analysis of Kenyan and Ugandan Newspaper Coverage - Thomas Ibrahim Okinda, Cyrus Kinyungu & (Covenant Journal of Communication, 2019)
Drawing on agenda-setting, priming and framing theories, this study compares the coverage of Migingo Island ownership dispute in Kenya’s Nation and The Standard and Uganda’s Monitor and New Vision newspapers. Contents published in 92 issues, between March 1 and December 31, 2009, were studied. The analysis established that both Kenyan and Ugandan newspapers published the conflict mainly in their interior pages with both sides identifying an inexistent borderline as a cause. However, the Kenyan press published the issue more frequently and front-paged a few of its stories while blaming the Ugandan security forces as the main cause of the conflict. Skewed coverage pattern, arising from reporters’ nationalistic behavior and desire to serve a domestic audience, was noticed. This has implications for conflict-sensitive reporting of interstate border conflicts in Africa.